2013
DOI: 10.1177/0269215513497735
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin injection into the forearm muscles for wrist and fingers spastic overactivity in adults with chronic stroke: a randomized controlled trial comparing three injection techniques

Abstract: Instrumental guidance may improve the outcome of botulinum toxin injections into the spastic forearm muscles of stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 23 publications
3
63
1
1
Order By: Relevance
“…In line with growing evidence of the usefulness of electrical stimulation/electromyography and ultrasonography guidance, the panelists agreed that localization techniques are essential for onabotulinumtoxinA treatment of all postures due to post-stroke spasticity (Picelli et al, 2012a;Picelli et al, 2012b;Picelli et al, 2014a;Picelli et al, 2014b;Grigoriu et al, 2015;Esquenazi et al, 2017;Simpson et al, 2017).…”
Section: Organizational Care Modelmentioning
confidence: 88%
“…In line with growing evidence of the usefulness of electrical stimulation/electromyography and ultrasonography guidance, the panelists agreed that localization techniques are essential for onabotulinumtoxinA treatment of all postures due to post-stroke spasticity (Picelli et al, 2012a;Picelli et al, 2012b;Picelli et al, 2014a;Picelli et al, 2014b;Grigoriu et al, 2015;Esquenazi et al, 2017;Simpson et al, 2017).…”
Section: Organizational Care Modelmentioning
confidence: 88%
“…A possible explanation might be the use of ultrasonography to identify target muscles; in fact, as reported by Henzel et al (2010), ultrasound localization may improve accuracy of needle placement, avoiding injection into vascular structures and reducing the potential risk of systemic diffusion of BoNT-A. Moreover, this technique can improve clinical outcome both in upper and lower limb PSS (Picelli et al 2014;Santamato et al 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Use of these techniques can optimize clinical efficacy. Although studies have shown that EMG-and ultrasonography-guided injection of BoNT is more likely to reach the targeted muscle as well as its endplate in treatment of spasticity, 17,18 it remains unclear whether injections using EMG or ultrasonography guidance result in greater functional improvement than nonguided injections. Although generally payers will not question EMG or ultrasound for BoNT, there are no clear payer policies on the use of guided injections, and their use depends on the experience and comfort level of the individual providers.…”
Section: Other Considerationsmentioning
confidence: 99%